Case Report: Primary low-grade dedifferentiated liposarcoma of the urinary bladder with molecular confirmation - Cui, Jian; Peng, Ran; Zhang, Yahan; Lu, Yang; He, Xin; Chen, Min; Zhang, Hongying (Frontiers in Oncology, 2023)
Liposarcoma originating from the urinary bladder is extremely rare. Only 6 cases of bladder liposarcoma have been reported and all have been described as myxoid liposarcoma. Notably, none of these cases underwent molecular detection. Here we reported a dedifferentiated liposarcoma (DDL) that occurred in the urinary bladder primarily in a 69-year-old Chinese woman with infrequent low-grade dedifferentiation. Computed tomography revealed an ill-defined solid mass on the anterior wall of the bladder. The patient underwent partial bladder resection. Histologically, the tumor cells with mild to moderate nuclear atypia were arranged in fascicular and storiform patterns, mimicking a low-grade fibroblastic tumor. In addition, scattered small foci of typical lipoma-like well-differentiated components were identified. Immunohistochemically, the tumor demonstrated positivity for MDM2, CDK4, and p16. Fluorescence in situ hybridization revealed MDM2 gene amplification in the neoplastic cells. Whole exome sequencing showed that this tumor also harbored CDK4, TSPAN31, and JUN amplification. The patient was alive with no evidence of disease at the latest follow-up (85 months after surgery). To the best of our knowledge, this is the first example of molecularly confirmed primary bladder liposarcoma and the first DDL in this site.